SUATU TINJAUAN TENTANG ALASAN MANUSIA MENTAATI HUKUM - Cecep Cahya Supena (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
The role of law in a country is absolutely necessary, because the law can be a guide or guide in organizing the life of society, nation and state. In addition, the law can also help prevent or avoid the occurrence of anarchic actions (arbitrarily) both from individual human beings to other human individuals, as well as from state authorities against every human being who is its people. This is because the purpose of the law is to create a safe, orderly, peaceful, just, safe, happy, prosperous, and useful society. Thus, the life of society, nation and state can run dynamically and in balance.